The Association Between the Classification of Early-onset Scoliosis and Smith Complications After Initiation of Growth-friendly Spine Surgery: A Preliminary Study. Issue 10 (November 2019) - Russo, Christen; Trupia, Evan; Campbell, Megan; Matsumoto, Hiroko; Smith, John; Samdani, Amer; Emans, John; Roye, David; Vitale, Michael
Abstract : Background: Early-onset scoliosis (EOS) is a complex, heterogeneous condition involving multiple etiologies, genetic associations, and treatment plans. In 2014, Williams and colleagues proposed a classification system of EOS (C-EOS) that categorizes patients by etiology, Cobb angle, and kyphosis. Shortly after, Smith and colleagues validated a classification system to report complications of growth-friendly spine instrumentation. Severity refers to the level of care and urgency required to treat the complication, and can be classified as device-related or disease-related complications. The purpose of this study was to investigate if C-EOS can be used as a reliable predictor of Smith complications to better risk stratify these young, surgical patients. Methods: This study queried retrospective data from a large multicenter registry with regard to growth-friendly spine instrumentation in the EOS population. One-hundred sixteen patients were included in final data analysis to investigate the outcomes of their growth-friendly procedures according to the Smith complication classification system. Results: There were 245 Smith complications distributed among 116 patients included in this study (2.1 complications per patient). The majority of the complications were device related requiring at least one unplanned trip to the operating room (Smith Device Complication IIA or IIB; 111 complications). There were no complications that caused abandonment of growth-friendly instrumentation (Smith Complication III) and no mortalities (Smith Complication IV). The most severely affected EOS group was the hyperkyphotic syndromic group with a major curve angle >50 degrees (S3+), with 3.4 complications per patient. The least affect EOS group was the hyperkyphotic congenital group with a major curve angle between 20 and 50 degrees, with 0.3 complications per patient. Conclusions: The C-EOS simplifies a complex pathology and the Smith complication classification scheme creates a language to discuss treatment of known complications of growth-friendly spine surgery. Although there is an association between more advanced C-EOS and Smith complications, there does not appear to be a correlation that can satisfy a risk stratification at this time. Level of Evidence: Level II.